The Baptist Contribution to Nineteenth Century Education for Women: An Examination of Moulton College and McMaster University - LeGendre, Carmelle Anne (My University, 1981)
In this work nineteenth century developments in education for women are examined within the context of transformations in the Canadian social structure. The admission of women to university education is analyzed not only as part of the limited democratization of the system, but also in terms of the expansion and redefinition of the 'proper sphere' of middle and upper class women. In accounting for why women were allowed access to higher education we present the underlying political and economic realities that shaped the arguments of those involved in the debate and final resolution of the conflict. The Baptist denomination, despite its small size, lack of general wealth and organizational difficulties, made an important contribution to the development of education in Ontario. Baptist democratic church organization, emphasis on the importance of individual salvation and evangelical orientation combined with other factors to produce a predisposition towards promoting education for girls and women. Specifically, the establishment and continued support of Moulton College and McMaster University constituted a unique achievement in educational endeavour.
Keywords: Sociology; Sociology